Persepsi Siswa terhadap Komunikasi Guru Pembimbing dalam Pelaksanaan Layanan Informasi (Studi Deskriptif terhadap Siswa SMP N 26 Padang) - novianti, ines (Konselor, 2013)
In fact at the school execution of information service less is effective caused by perception of student to communications teacher counsellor. Target of research lay open perception of student to communications teacher counsellor in execution of information service in SMP N 26 Field. This Research use quantitative approach of descriptive type, intake of Stratified Sampling sampel. result of research indicate that perception of student to communications teacher counsellor in execution of good enough information service